Risiko Operasional Pada Pengembangan Unit Cabin Hostel Di Inap At Capsule Hostel – Jakarta - Steven Messakh (Jurnal Syntax Transformation, 2021)
Construction of the Inap At Capsule cabin unit in Jakarta in an effort to improve service quality. The purpose of this study is to identify business processes, calculate the magnitude of risk, and determine risk mitigation in the development of cabin hostel units at Inap At Capsule Hostel – Jakarta. The research method is quantitative. The results of this study include, the business process of developing cabin hostel units at capsules, there are three stages, the planning stage, the design stage, and the implementation stage. The three biggest risks are obtained, the scope of project work is unclear, does not get a building permit, and the development design is not appropriate. For the risk that the scope of project work is not clear, the mitigation is that the project is carried out by considering the load; fund; and time available, re- checking the project certainty to the relevant contractor. For the risk of not getting a building permit, the mitigation is to ensure that every required document is required in the manufacture of IMB, not to carry out construction in a hurry, to improve internal communication from the vertical organizational structure, and to carry out regular follow-up regarding permits to the relevant agencies. For the risk of design design that is not suitable, the mitigation is consulting with people who are experts in the field of development design, using the design as needed, making sure the design used is in accordance with field conditions, not conducting design consultations before ensuring design approval